Economic Resilience with An Exchange Rate Peg : The Barbados Experience, 1985-2000 - Craigwell, Roland (IMF Working Papers; Working Paper ;, 2003)
This paper discusses the institutional arrangements for exchange rate targeting in Barbados and the critical role they played in the policy response to its balance of payments crisis of 1991-92. The framework featured ongoing cooperation between the central bank and the Ministry of Finance, and the use of a forecast model which highlighted the size of fiscal adjustment needed to secure foreign reserves adequate to maintain the exchange rate peg.